FGF6 promotes cardiac repair after myocardial infarction by inhibiting the Hippo pathway. Issue 5 (30th March 2022) - Hu, Zhicheng; Chen, Peng; Wang, Linlin; Zhu, Yu; Chen, Gen; Chen, Yunjie; Hu, Zhenyu; Mei, Lin; You, Weijing; Cong, Weitao; Jin, Litai; Wang, Xu; et al.
Abstract: Objectives: Myocardial infarction (MI) commonly occurs in patients with coronary artery disease and have high mortality. Current clinical strategies for MI still limited to reducing the death of myocardial cells but failed to replace these cells. This study aimed to investigate the role of fibroblast growth factor 6 (FGF6) in enhancing the proliferative potential of cardiomyocytes (CMs) after ischemic injury via the Hippo pathway. Materials and Methods: Expression of FGF6 protein was analysed in mice with MI induced by ligation of the left anterior descending coronary artery. Activation of the Hippo pathway and the proliferation potential were examined in ischemic CMs, treated with FGF6 protein or transfected with an adeno‐virus carrying FGF6 sh‐RNA. Immunofluorescence staining and western blotting were performed to assess the relationship between FGF6 and the Hippo pathway. Results: We found that FGF6 expression was significantly increased in the MI mouse model. Knockdown of FGF6 synthesis resulted in poorer heart function after MI. By contrast, treatment with recombinant human FGF6 protein improved heart function, reduced infarct size, and promoted cardiac repair. Additionally, FGF6 restrains the activation of the Hippo pathway and subsequently promotes nuclear accumulation of YAP. This was largely counteracted by treatment with extracellular signal‐regulated kinase 1/2 (ERK1/2) inhibitor U0126. Conclusion: FGF6 inhibits the Hippo pathway via ERK1/2, and facilitates nuclear translocation of YAP, and thereby promotes cardiac repair after MI. Abstract : Schematic illustration of the protective effects of FGF6 on cardiomyocytes under ischemic conditions. Myocardial infarction would cause the loss of a huge number of cardiomyocytes. In this study, we revealed that FGF6 restrains the Hippo pathway via ERK, and promotes YAP nuclear translocation then increase cardiomyocytes proliferation and cardiac regeneration.